Voltammetric determination of ascorbic acid in foodstuffs using modified carbon paste electrodes - Nováková, Marcela; Kalcher, Kurt; Schachl, Klemens; Komersová, Alena; Bartoš, Martin; Vytřas, Karel (My University, 1997)
Application of differential pulse cathodic stripping voltammetry for determination of ascorbic acid in foodstuffs have been investigated using a carbon paste electrode modified by cobalt(II) phthalocyanine, which was found to facilitate its oxidation and to decrease the necessary overvoltage. The method showed a good linearity up to 70 ppm of ascorbic acid with a detection limit of 0.8 ppm. When applied to analyse the real samples (fruit juices), the results agreed well with those obtained by traditional titrimetric determination.